JOINT SYSTEM DESIGN FOR REFUGEE TENTS DISTRIBUTION IN POST DISASTER REHABILITATION STAGE - Muhammad Taufik Abdalla 17514025, Raja
Due to post-disaster treatment, residential tents become a primary requirement that needs to be fulfilled for each refugee. The needs for security, privacy, and sanitation leads to decent residential demands. On emergency response stage, the refugees live in mass inside the barrack tent with limited facilities. Entering the rehabilitation phase, residential tents become crucial requirements that help them rebuild their family as the situation improves. However, in Indonesia, there is a lack of tent supply due to a huge demand according to the number of refugees which makes it hard to be fulfilled. Most tent design in Indonesia uses iron pipe frame as its construction, along with the tarpaulins as the cover. The components of the tents are considered heavy and make it difficult to distribute. On the other hand, the usage of material found around the disaster area, such as bamboo that could be used as the tent’s construction frame is a great potential to replace the iron frame and reduce the logistic load of the distribution. But this bamboo based tent’s construction done by the volunteers and refugees does not meet the specified post-disaster family residential standard. Therefore, a supporting media is surely needed to ensure the standardization of its construction. The offered solution in this research is a delivery of tent package in the form of tarpaulins and joint system which functioned as a standardization media in the family tent construction, as well as reducing the weight of its logistics that will ease the distribution of the post-disaster rehabilitation family tent.